A Comprehensive Analysis of Glycemic Variability and Time in Ranges Assessed using CGM in Diabetic People with diabetes with Microvascular Complications: A Single-Center Retrospective Real-World Evidence Study on Indian Population - Dr Mudit; Srivani Palukuri; Saurav Deka (British Journal of Healthcare and Medical Research, 2022)
Background: Regular assessment of glycemic variability is important to maintain good control of glycemic levels resulting delaying the onset or progression of microvascular complications. Objective: To investigate association of glycemic variability (GV) and time in glucose ranges measured using CGM with diabetes microvascular complications. Methodology: Retrospective CGM data collected for total 214 types 1 and 2 people with diabetes with (G1) and without (G2) microvascular complications. The daily glucose target range (TIR) was 70-180 mg/dL and variations in time above range (TAR), >180 mg/dL, and time below range (TBR), <70 mg/dL, considered as glucose excursions. The GV was assessed by SD, CV, MAGE, and MODD. Results: On average, 7 and 12% of G1 people with diabetes had spent higher time in <54 (>1%) and >250 mg/dL (>5%) glucose values. In G1, around 15% of people with diabetes had hypoglycemic events (>15 mins/day) than G2. In insulin taking people with diabetes, MAGE values were about 20 (G1) and 15% (G2) higher than their respective group averages. The logistic regression had resulted significant association of TBR-54 [OR 2.7; (95% CI 1.2-6.1)] and CV [OR 1.1 (1.0-1.1)] with complications. The risk increased 1.5 times [OR 4.1 (1.4-11.7)] with night-time and 2.7 times [OR 7.5 (2.1-26.4)] during daytime hypoglycemia (≥45 minutes). Conclusion: For every 1% increase (15 minutes) of time spent in <54 mg/dL had increased 2.7 times the risk for complications. It is equally important to focus on achieving % of time spent in both target glycemic values and hyper and hypoglycemia to the extent possible.